2004
DOI: 10.1378/chest.126.6.1840
|View full text |Cite
|
Sign up to set email alerts
|

New Computerized Tomogram (CT) Indices for Pectus Excavatum: Tools for Assessing Modified Techniques for Asymmetry in Nuss Repair

Abstract: The results of our study indicate that extensive small airway abnormalities may be associated with NFA, and that these abnormalities are partially reversible after the successful control of asthma symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Pathological changes in these small structures can be imaged only indirectly due to limited spatial resolution of the current imaging techniques [5, 25]. Air trapping reflects changes in small airways (below HRCT spatial resolution) [24, 26]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pathological changes in these small structures can be imaged only indirectly due to limited spatial resolution of the current imaging techniques [5, 25]. Air trapping reflects changes in small airways (below HRCT spatial resolution) [24, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [24] observed increased air trapping in patients with moderate and severe asthma and even in mild asthma as compared to normal control subjects. In the study of Arakawa and Webb [27] air trapping on expiratory HRCT scans in patients with no abnormalities on inspiratory scans was most often associated with obliterative bronchiolitis and asthma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations